PERBANDINGAN PEMBERHENTIAN PRESIDEN DALAM SISTEM PEMERINTAHAN PRESIDENSIAL DI INDONESIA, KOREA SELATAN, AMERIKA SERIKAT: Comparison Of The Removal Of Presidents In Presidential Systems In Indonesia, South Korea, And The United States - Fadillah, Evi; Sulistyowati, Tri (Faculty of Law, Universitas Trisakti, 2024)
In a presidential system of government, the President is the head of state with extensive powers, and their term in office is fixed until the end of their government's term. To balance the President's authority, a system of oversight leading to the process of presidential removal is necessary. The issue addressed here is how the removal of the President during their term in office is carried out in Indonesia, South Korea, and the United States, and what role Congress/National Assembly plays in the process of presidential removal. This research employs a normative juridical approach, descriptive in nature, drawing from secondary and primary data sources, and arriving at conclusions through deductive logic. The findings of this study are as follows: the procedure for the removal of the President in Indonesia, before the amendment of the 1945 Constitution, was regulated under Article 8, while after the amendment, it is regulated under Articles 7A and 7B. In South Korea, the procedure is governed by Article 111 of the 1987 Constitution of the Republic of Korea, and in the United States, it is regulated by Article 1, Section 5, of The Constitution of the United States. The reasons for presidential removal in each country are based on the commission of criminal acts by the President, with the Indonesian People's Consultative Assembly (MPR), the U.S. Congress serving as determinants of whether the President should be removed or not, while in South Korea, it is the Constitutional Court of Korea that makes the determination